The role of Primary Health Care (PHC) nurses in breaking the cycle of diseases and environmental damage caused by contaminated water in vulnerable communities: A integrative review (Research, Society and Development, 2025)
The study aimed to analyze the role of Primary Health Care (PHC) nurses in breaking the cycle of diseases and environmental damage caused by contaminated water in vulnerable communities, through an integrative literature review. An integrative descriptive review was carried out with a qualitative approach, using databases such as LILACS, VHL, SciELO and PubMed. 11 articles published between 2016 and 2024 were selected, which addressed the role of PHC nurses in coping with diseases related to contaminated water. The analysis focused on strategies, challenges and impacts of the interventions. The main strategies adopted by PHC nurses include health education, epidemiological surveillance, intersectoral articulation, and the use of low-cost technologies. The challenges faced are the lack of resources, work overload and the need for continuous training. The interventions led by these professionals had a positive impact on the reduction of environmental damage and the improvement of collective health, especially in peripheral and rural regions. PHC nurses play a crucial role in coping with diseases related to contaminated water, promoting preventive and educational practices that reduce morbidity and mortality and strengthen the resilience of communities. However, challenges such as lack of resources and work overload need to be overcome to maximize the impact of these interventions. Investments in infrastructure, training, and public policies are essential to ensure the effectiveness and sustainability of actions.